ANALISIS PROSES PENERIMAAN MAHASISWA BARU POLITEKNIK LP3I JAKARTA KAMPUS CIKARANG - Winarto, Tri; Nurjanah, Siti (JURNAL LENTERA BISNIS, 2026)
New Student Admissions (PMB) is the abbreviation for New Student Admissions. It is the process undertaken by universities to recruit and select prospective new students who meet established criteria. The new student admission process at the LP3I Jakarta Polytechnic, Cikarang Campus, still faces several obstacles that could hamper the efficiency and effectiveness of overall academic activities. Some of these issues include the suboptimal registration system. Some processes, such as physical file collection, document verification, and test scheduling, are still carried out manually. This poses a risk of delays, data entry errors, and lack of accessibility for prospective students from outside the region. In today's digital age, such system limitations can be a barrier to attracting applicants seeking ease and speed in the administrative process. Based on research and analysis conducted on the new student admission process at the LP3I Jakarta Polytechnic, Cikarang Campus, it is systematic and structured, starting with the promotion and outreach stages, registration, administrative selection, interviews, and the announcement of selection results and re-registration. Each stage plays a crucial role in attracting prospective students who meet the institution's criteria. Standard operating procedures (SOPs) have been implemented effectively, although some shortcomings remain, such as delays in data entry or technical issues with the online registration system. This indicates that, while the process is well-organized, regular evaluation and service quality improvement are still needed.